Efektifitas Media Boneka Upin-Ipin dalam Meningkatkan Kemampuan Mengenal Huruf Hijaiyah pada Kelompok A di Pos PAUD Bougenville 2 Ngawen Sidayu Gresik - Nina Nuriyah Ma’arif; Nur Azizah (Atthiflah: Journal of Early Childhood Islamic Education, 2020)
This article discusses the effectiveness of using the Upin-Ipin doll media in increasing the ability of a group of students in the early childhood education (PAUD) in recognizing hijaiyah letters at Pos PAUD Bougenville 2 Ngawen Sedayu Gresik. By using the classroom action research method, this study shows that the usage of the Upin-Ipin doll has resulted in an increase the ability of students of Pos PAUD Bougenville 2 Ngawen Sidayu Gresik in reading hijaiyah letters. It can be seen from the increase of each student's score in cycle I (75%) to 92% in cycle II. It is also found that the overall percentage in cycle I (50%) increases (80%) in the overall percentage in cycle II.